SCOUT THERAPY SENYUM LUAR BIASA (ST â SLB) - Andini, Fajar Putri; Nindita, Cinanthya Lila (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2014)
The concept of youth as the hope of the nation is now barely able to appear on the surface. Through Scouting, can build morale not to mention who have mental retardation. SLB C Yakut Purwokerto an Extraordinary School consisting of students kindergarten, elementary, junior high, and high school levels who have different disabilities. State remains unstable learners into problems and difficulties of the school to seek Trustees who are able to educate Scouting in their school, during which teaches learners are scouting for their own teachers. Therapy Through the Scout method, have the view that they are intended to have the appropriate proportion of the age when given an understanding of the scout fun but still educational, teaching a variety of useful knowledge for learners, the implementation will be more easily realized with the provision of a lightweight material interspersed with games, singing and clapping typical scout that will make students like and not boring. The goal is to minimize flapping and tantrums activity by pointing to activities that are more useful, especially Scout, improving the response of children to interact and socialize, hone skills and proficiency of children with special needs in SLB C Yakut Navan, foster a sense of patriotism through scoutin, creating a lightweight and fun method for mentally disabled children. Keywords: Scout, Extraordinary Smiles, Flapping, Tantrum